Perioperative Nurse Educators: Rapid Response to the COVID‐19 Pandemic. (3rd February 2021) - Peneza, Daphny; White‐Edwards, Karen Y.; Bricker, Crystal; Mahabee‐Betts, Mary; Wagner, V. Doreen
ABSTRACT: During the initial response to the coronavirus disease 2019 (COVID‐19) pandemic, hospital leaders limited or halted the scheduling of elective surgical procedures. Perioperative nurse educators participated in a rapid response to develop innovative strategies and use a variety of modalities to provide information and education activities for staff members who were reassigned to different hospital areas. Residency program educators used alternative teaching methods to accommodate the lack of clinical rotations and allow orienting nurses to progress in an OR nurse residency program. Limited access to ORs and social distancing rules prevented nursing students from completing clinical rotations in health care settings, and academic educators developed flexible solutions to meet the students' needs. Perioperative educators can use guidance from national and international organizations to assist leaders and staff members with managing patient care during the pandemic. This article presents specific information on perioperative nurse educator roles and responses during the pandemic.